2012
DOI: 10.14207/ejsd.2012.v1n3p383
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Equality work for Sustainable Development in Central Africa Countries? Some Empirical Lessons

Abstract: It is commonly argued that Central Africa countries need economic growth and gender equality to ensure economic well-being and improve the living standards of the population. This paper, based on the Kuznets curve associated to environmental analysis, aims to analyze the relationship between gender equality and sustainable development. The cross-sectional analysis, with data from 11 countries in Central Africa in 2010, was used. Results find a positive correlation between gender equality and sustainable develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Tchouassi [1] , identified some risks associated with mobile banking and these include, insecure information when accessing services as the platform requires the submission of personal information through a text messaging platform. This can attract hackers who can try to access personal information through insecure Wi-Fi hotspots [15] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tchouassi [1] , identified some risks associated with mobile banking and these include, insecure information when accessing services as the platform requires the submission of personal information through a text messaging platform. This can attract hackers who can try to access personal information through insecure Wi-Fi hotspots [15] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a plethora of mobile banking services by most financial institutions to customers in recent years as a way of boosting performance [1] . A lot of interest has now been generated as a result of the rollout of these services in developing countries among various players in the financial services sector of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…They found that social inclusion indicators need to be subsidized and addressed to improve SD. Gender equality was identified to be one of the primary drivers of SD (Tchouassi, 2012). More specifically, Tchouassi (2012) employed a cross-sectional analysis to examine the nexus between gender equality and SD in 11 Central African countries in 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The links between women's economic empowerment and economic development and the positive correlation between girls' education and sustainable development is well documented. Equal access to education and employment for females not only benefits women, but also the families and communities they nurture (Ngugi, M. and Muthima, P., 2017;Tchouassi, 2012;Van den Bergh Collier, E., 2017;UNESCO, 2020;ILO, 2020). Girls in low-income countries who receive secondary education are 63% less likely to marry than girls without it and have fewer and healthier children.…”
Section: Lacking Connection To African Feminist and Post-colonial Sch...mentioning
confidence: 99%